High strength and high toughness hydrogen separation composite membrane

Three layers of structures are designed in the hydrogen separation composite membrane, including external enhanced membrane layers, purified membrane layers, and internal enhanced membrane layers, and load catalysts in the enhanced membrane layer. The problem of decreased strength realizes the efficient purification and stable production of high -purity hydrogen.

CN222400984UActive Publication Date: 2025-01-28SHANGHAI SHAANXI COAL HIGH-TECH RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202323639193.9
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-01-28
Estimated Expiration
2033-12-29

AI Technical Summary

Technical Problem

The existing hydrogen separation composite membranes have reduced mechanical strength under high pressure differential environments, weakened resistance to deformation, prone to rupture and failure, and are difficult to meet the purification requirements of ultrapure hydrogen.

Method used

Design a three -layer hydrogen composite film that includes external enhanced membrane layers, purifying membrane layers and internal enhanced membrane layers. By adding enhanced membrane layers on both sides of the metal film, the overall strength and toughness are improved, and the load in the enhanced membrane layer is enhanced. The catalyst is improved to improve the hydrogen purification effect.

Benefits of technology

Effectively improve the structural strength and durability of the hydrogen separation composite film, improve the purification performance of hydrogen, ensure the production efficiency of high -purity hydrogen, and maintain good packaging performance in high -pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222400984U_ABST
    Figure CN222400984U_ABST
Patent Text Reader

Abstract

The utility model provides a high-strength and high-toughness hydrogen separation composite membrane, which comprises a purification membrane layer and is characterized by comprising an inner reinforced membrane layer arranged on a raw material gas side of the purification membrane layer and an outer reinforced membrane layer arranged on a purified gas side of the purification membrane layer, the thickness of the purification film layer is 20-50 [mu] m; the thickness of the inner reinforced film layer or the outer reinforced film layer is 20-40 [mu] m, preferably 25 [mu] m. Furthermore, at least one part of the inside and the surface of the inner reinforced film layer is loaded with at least one of a hydrogen production catalyst and a carbon capture catalyst. According to the utility model, the reinforced film layers are added on the two sides of the metal film without changing the high hydrogen permeability of the metal film, so that the overall strength and toughness of the film are improved, and the packaging capability is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of hydrogen purification, in particular to a high-strength and high-toughness hydrogen separation composite membrane used for purifying high-purity hydrogen (5N and above). Background Art

[0002] With the development of society, carbon tax as an emerging form of taxation has attracted more and more attention from countries around the world. Hydrogen, as a secondary energy source with abundant sources, green and low carbon, and wide application, can replace carbon from the root and achieve the goal of reducing carbon emissions. In addition to its energy properties, hydrogen energy also has a wide range of applications in the industrial field. On the one hand, hydrogen can be used in the production of synthetic ammonia, manufacturing chemicals, metal smelting and food processing. On the other hand, hydrogen is needed as fuel, protective gas, reducing gas, etc. in the production process of many special industries. For example, high-purity hydrogen in semiconductor processing, hydrogen metallurgy for low-carbon transformation of the steel industry, hydrogen quenching of steel tempering, hydrogen reduction of powder metallurgy and float glass, etc. In particular, high-purity hydrogen with a purity of 99.999% and above is an indispensable carrier gas raw material in the semiconductor industry. It is indispensable in the extraction of semiconductor materials silicon and germanium, epitaxial growth in the production of semiconductor devices, device sintering and other processes, and its purity has an important impact on product quality control.

[0003] The membrane separation method is used in the production of ultrapure hydrogen because of its simple process flow and high hydrogen purity. In particular, the metal separation membrane is currently the most effective technical method for producing ultrapure hydrogen (99.9999%). With the consumption of precious metal palladium resources, the cost of palladium and palladium-based alloys has gradually increased, and reducing the membrane thickness has become a common method to reduce costs and further increase the hydrogen purification flow rate. However, as the thickness of the metal film decreases (reaching the micron level), especially for metal films with large specific surface areas, the mechanical strength of the membrane decreases, and the ability to resist deformation is weakened. When serving in a high pressure difference environment, it is very easy to rupture and fail. The current mainstream method is to use porous ceramics as a support, plate a thin metal film on the surface or directly contact the ceramic support on one side of the metal film, and then encapsulate it. This method has at least the following problems: first, the purity of hydrogen prepared by the composite membrane of palladium / palladium-based alloy-porous ceramic structure is difficult to meet the ultra-pure requirements; second, the design of the ceramic support body loaded with palladium membrane will lead to poor airtightness at both ends and low packaging reliability; third, after the metal film in direct contact with the support body is compressed, the deformation degree of the membrane and the support body is different, which can easily cause the film to wrinkle and deform, and eventually rupture and fail. Utility Model Content

[0004] Due to the above-mentioned defects in the prior art, the utility model provides a high-strength and high-toughness hydrogen separation composite membrane. Without changing the high hydrogen permeability performance of the metal film, a strengthening film layer is added on both sides of the metal film, which not only improves the overall strength and toughness of the film, but also improves the packaging capacity.

[0005] To achieve the above-mentioned purpose, the utility model provides a hydrogen separation composite membrane, including a purification membrane layer, characterized in that an outer strengthening membrane layer is arranged on the raw gas side of the purification membrane layer and an inner strengthening membrane layer is arranged on the purified gas side of the purification membrane layer; the thickness of the purification membrane layer is 20 to 50 μm; the thickness of the outer strengthening membrane layer or the inner strengthening membrane layer is 20 to 40 μm, preferably 25 μm.

[0006] Furthermore, the composite membrane is in the shape of a sheet or a tube.

[0007] Furthermore, at least one of the hydrogen production catalyst and the carbon capture catalyst is loaded on at least one portion of the interior and the surface of the outer reinforcement membrane layer.

[0008] Furthermore, the raw gas includes hydrogen, nitrogen, carbon monoxide, carbon dioxide and other impurity gases.

[0009] Furthermore, in the raw gas, hydrogen accounts for 0-90 vol%, nitrogen accounts for 0-30 vol%, carbon monoxide accounts for 0-10 vol%, carbon dioxide accounts for 0-30 vol%, and the remaining impurity gases account for 0-5 vol%.

[0010] Furthermore, at least one of the interior and the surface of the outer strengthening film layer is loaded with an impurity gas adsorption conversion catalyst, and the catalyst can be used in a mixed atmosphere with a low hydrogen content.

[0011] Furthermore, the remaining impurity gases include one or more of water vapor, ammonia, methane, methanol, etc.; the impurity gas adsorption conversion catalyst is capable of adsorbing hydrocarbon atmosphere and is one or more of nickel-based, iron-based, copper-based or zirconium-based catalysts.

[0012] Furthermore, the material of the outer strengthening film layer is one or more of inorganic fiber, porous metal, porous alloy; the material of the inner strengthening film layer is one or more of inorganic fiber, porous metal, porous alloy; the outer strengthening film layer and the inner strengthening film layer can be the same or different types of materials. Among them, the inorganic fiber is one of glass fiber, alumina ceramic fiber, silicon carbide fiber, boron fiber or a composite thereof, the porous metal is one of Al, Cu, Ni, Ti metal, and the porous alloy is one of porous NiCrFe, porous ZnCu, porous NiCu, porous NiCrW, porous NiFe, porous high entropy alloy, porous stainless steel, and porous titanium alloy. The inorganic fiber can be prepared by spraying, sol method, high temperature sintering method, and coating. The porous metal and porous alloy can be prepared by powder metallurgy, physical deposition, chemical deposition, chemical plating, and electroplating.

[0013] Further, the purification membrane layer (102) is one of a palladium metal layer, a palladium-based alloy layer, a non-palladium metal layer or a non-palladium-based alloy layer; wherein the non-palladium metal is one of a vanadium metal, a niobium metal and a tantalum metal, and a hydrogen dissociation catalyst is plated on the surface; the non-palladium-based alloy is one of a vanadium-based alloy, a niobium-based alloy and a tantalum-based alloy, and a hydrogen dissociation catalyst is plated on the surface. There is no strict limitation on the method of plating the hydrogen dissociation catalyst layer on the surface of the purification membrane, and one or more methods such as physical vapor deposition, chemical vapor deposition, electroplating, chemical plating, sintering and laser cladding can be used.

[0014] Furthermore, the hydrogen production catalyst is one or more of a platinum group catalyst, graphene, a transition metal nitride, a transition metal sulfide and a transition metal carbide.

[0015] Compared with the prior art, the above utility model has the following advantages or beneficial effects:

[0016] The hydrogen purification composite membrane of the utility model is a three-layer structure of an outer strengthening membrane layer-a purification membrane layer-an inner strengthening membrane layer, which can effectively improve the structural strength of the purification membrane and the durability of the membrane, thereby effectively improving production efficiency. Combined with the catalyst in the strengthening membrane layer, direct contact of crude hydrogen with the purification membrane is avoided. The composite membrane has the advantages of high strength and toughness, long hydrogen permeation durability, wide operating pressure range, and good packaging performance, and has broad application prospects in high-pressure environments and the field of industrial crude hydrogen purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention and its features, appearance and advantages will become more apparent by reading the detailed description of the non-limiting embodiments with reference to the following drawings. The same reference numerals indicate the same parts in all the drawings. The drawings are not drawn completely to scale, and the emphasis is on illustrating the subject matter of the present invention.

[0018] Figure 1 A schematic diagram of a composite membrane structure according to an embodiment of the present invention;

[0019] Figure 2 The results of the hydrogen pressure resistance test of the composite membrane prepared in Example 1 at 300°C;

[0020] Figure 3 Schematic diagram of the three-dimensional and cross-sectional structure of the composite membrane tube in Example 2;

[0021] Figure 4 This is a schematic diagram of the composite membrane structure prepared in Example 3;

[0022] Figure 5 The hydrogen purification durability test results of the composite membranes prepared in Examples 3 and 4 at 300°C;

[0023] Figure 6The hydrogen purification results of the composite membrane prepared in Example 4 at 300°C and 400°C;

[0024] In the attached drawings: 101, outer strengthening membrane layer; 102, purification membrane layer; 103, inner strengthening membrane layer; 104, catalyst layer. DETAILED DESCRIPTION

[0025] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. It should be understood that all of these exemplary embodiments described are only partial embodiments and examples of the present utility model, rather than all of them. On the contrary, these exemplary embodiments are provided so that those skilled in the art can more thoroughly understand the present disclosure and can more completely convey the technical content of the present disclosure to those skilled in the art. In addition, the metals, alloys, catalysts, fibers, etc. involved in the following embodiments and examples can be selected according to demand, and are all known materials and are commercially available.

[0026] See also Figure 1 The following embodiment provides a sheet-shaped or tubular hydrogen separation composite membrane, comprising a purification membrane layer 102, an outer strengthening membrane layer 101 arranged on the raw gas side of the purification membrane layer 102, and an inner strengthening membrane layer 103 arranged on the purified gas side of the purification membrane layer 102; the thickness of the purification membrane layer 102 is 20 to 50 μm; the thickness of the outer strengthening membrane layer 101 or the inner strengthening membrane layer 103 is 20 to 40 μm, preferably 25 μm.

[0027] As a preferred embodiment, further: at least one of a hydrogen production catalyst and a carbon capture catalyst is loaded on at least one portion of the interior and the surface of the outer strengthening membrane layer 101 .

[0028] As a preferred embodiment, further: the raw gas includes hydrogen, nitrogen, carbon monoxide, carbon dioxide and other impurity gases. Preferably, hydrogen accounts for 0-90 vol%, nitrogen accounts for 0-30 vol%, carbon monoxide accounts for 0-10 vol%, carbon dioxide accounts for 0-30 vol%, and other impurity gases account for 0-5 vol% in the raw gas.

[0029] As a preferred embodiment, further: at least one part of the interior and the surface of the outer strengthening film layer 101 is also loaded with an impurity gas adsorption conversion catalyst. The catalyst can be used in a mixed atmosphere with a low hydrogen content. Specifically, the remaining impurity gases include one or more of water vapor, ammonia, methane, methanol, etc.; the impurity gas adsorption conversion catalyst can adsorb hydrocarbon atmospheres and is one or more of nickel-based, iron-based, copper-based or zirconium-based catalysts.

[0030] The utility model does not strictly limit the type of membrane layer in the composite membrane. Preferably, the material of the outer strengthening membrane layer 101 is one or more of inorganic fiber, porous metal, and porous alloy; the material of the inner strengthening membrane layer 103 is one or more of inorganic fiber, porous metal, and porous alloy; the outer strengthening membrane layer 101 and the inner strengthening membrane layer 103 can be the same or different types of materials. Among them, the inorganic fiber is one of glass fiber, alumina ceramic fiber, silicon carbide fiber, boron fiber or a composite thereof, the porous metal is one of Al, Cu, Ni, and Ti metals, and the porous alloy is one of porous NiCrFe, porous ZnCu, porous NiCu, porous NiCrW, porous NiFe, porous high entropy alloy, porous stainless steel, and porous titanium alloy. The inorganic fiber can be prepared by spraying, sol method, high temperature sintering method, and coating. The porous metal and porous alloy can be prepared by powder metallurgy, physical deposition, chemical deposition, chemical plating, and electroplating. The purification membrane layer 102 is one of a palladium metal layer, a palladium-based alloy layer, a non-palladium metal layer or a non-palladium-based alloy layer; wherein the non-palladium metal is one of vanadium metal, niobium metal and tantalum metal, and a hydrogen dissociation catalyst is plated on the surface; the non-palladium-based alloy is one of vanadium-based alloy, niobium-based alloy and tantalum-based alloy, and a hydrogen dissociation catalyst is plated on the surface. There is no strict restriction on the method of plating the hydrogen dissociation catalyst layer on the surface of the purification membrane, and one or more methods such as physical vapor deposition, chemical vapor deposition, electroplating, chemical plating, sintering and laser cladding can be used. Preferably, the hydrogen production catalyst is one or more of a platinum group catalyst, graphene, transition metal nitride, transition metal sulfide and transition metal carbide.

[0031] To further help understand the technical solution of the present utility model, the technical solution of the present utility model is described in more detail below through several specific implementation examples.

[0032] Example 1:

[0033] This example provides a sheet-like composite membrane for hydrogen purification, a glass fiber reinforced membrane layer-palladium silver purification membrane layer-glass fiber reinforced membrane layer, and its structural schematic diagram is as follows: Figure 1 As shown, it includes a glass fiber outer reinforcement film layer 101 located on the coarse hydrogen side, a dense Pd 75 Ag 25 Alloy purification membrane layer 102 and glass fiber inner strengthening membrane layer 103 located on the pure hydrogen side. The purification membrane layer 102 is used after mechanical grinding and polishing, with a diameter of 100 mm and a thickness of 30 μm. The glass fiber outer strengthening membrane layer 101 and the inner strengthening membrane layer 103 achieve the expected pore effect through inorganic pore-forming agents to meet the transmission requirements of raw gas and product gas.

[0034] Preferably, the outer strengthening membrane layer 101 and the inner strengthening membrane layer 103 made of glass fiber are obtained in different colors by using inorganic dyes, so as to distinguish the inner and outer sides of the sheet-like hydrogen separation composite membrane during the production process.

[0035] Specifically, the outer strengthening membrane layer 101 and the inner strengthening membrane layer 103 made of glass fiber are connected to the purification membrane layer 102 by gluing, which can enhance the strength of the purification membrane layer and make the composite membrane less likely to break in a high pressure difference working environment.

[0036] Alternatively, if the gas flow rate and pressure requirements are not high, only the glass fiber outer reinforcement membrane layer 101 and the purification membrane layer 102 may be retained. The composite membrane degenerates from a three-layer structure to a two-layer structure.

[0037] Specifically, in order to maintain high hydrogen transmission performance, the thickness of the outer strengthening film layer 101 and the inner strengthening film layer 103 should be controlled at about 25 μm.

[0038] The composite membrane in this example is bonded to the purifier frame by an inorganic high temperature resistant adhesive or brazing to form a single purifier. The purifier is used to conduct a hydrogen purification test, and the test method is as follows:

[0039] First, the prepared purifier is tested for helium. When the helium leak rate is less than 10 -12 Pa.m 3 / s, place the prepared purifier into a heat treatment furnace. Check the connection status of the gas pipelines upstream and downstream of the purifier. Then, use inert gas to perform overall air tightness tests and upstream and downstream air tightness tests on the purifier respectively. After the test is correct, the purifier is vacuum-heated at a heating rate of 5 to 10°C / minute, and kept warm for half an hour after reaching the target temperature. Then, the raw gas at the target pressure is introduced upstream, and the downstream is connected to the atmosphere or gas purging is performed. Record the downstream hydrogen flow at the target temperature and pressure to obtain the required data.

[0040] The composite membrane pressure resistance test is carried out under constant temperature conditions, with the upstream inlet pressure of the composite membrane changed. The test time at the same pressure is 10 minutes, and a set of data is recorded every 1 minute to observe the change of the hydrogen flow through the purifier with the test pressure. The hydrogen purification endurance test method is to maintain constant temperature and pressure for 10 hours, and record the change of the hydrogen flow through the purifier with the test time.

[0041] The operating temperature of the purifier is 300℃, the upstream and downstream pressure difference range is 15-20bar, the raw gas composition is 95vol.%H2+5vol.%CO2, and the pressure test results are as follows Figure 2 As shown. The horizontal axis in the figure is time t, the unit is minutes, written as min. The vertical axis is flow J, the unit is mol H2 m -2 s -1, which represents the hydrogen flow rate through a unit area per unit time. Figure 2 The results show that when the composite membrane works within this pressure difference range for a certain time t, the hydrogen production rate J is stable and the hydrogen purification performance is good.

[0042] Example 2:

[0043] This example provides a tubular composite membrane for hydrogen purification, which is a glass fiber reinforced membrane layer-palladium metal purification membrane layer-glass fiber reinforced membrane layer. The schematic diagram of its structure is as follows: Figure 3 As shown, it includes an outer strengthening membrane layer 101 (coarse hydrogen side) made of glass fiber, an inner strengthening membrane layer 103 (pure hydrogen side) made of glass fiber, and a dense Pd metal purification membrane layer 102.

[0044] Specifically, Figure 3 The purification membrane layer 102 in the middle tubular composite membrane is used after mechanical grinding and polishing, and has an effective length of 200 mm, an outer diameter of 6 mm, and a wall thickness of 50 μm.

[0045] Specifically, in order to maintain high hydrogen transmission performance, the thickness of the outer strengthening film layer 101 and the inner strengthening film layer 103 made of glass fiber is controlled to be about 20 μm.

[0046] Example 3:

[0047] See also Figure 4 This example provides a sheet-shaped composite membrane of glass fiber reinforced membrane layer-vanadium-based purification membrane layer-glass fiber reinforced membrane layer for hydrogen purification, comprising an outer reinforced membrane layer 101 (crude hydrogen side) of glass fiber, an inner reinforced membrane layer 103 (pure hydrogen side) of glass fiber, a dense V-based alloy purification membrane layer 102, and a catalyst layer 104 supported by the outer reinforced membrane layer 101. The performance of the catalyst layer 104 is preferably a nickel-based catalyst, specifically a mixture of Ni, Al2O3 and other additives. The catalyst in the catalyst layer 104 can be supported inside and / or on the surface of the outer reinforced membrane layer 101.

[0048] Specifically, after mechanical grinding and polishing, the vanadium metal is chemically plated with a 100nm thick palladium catalyst layer on both sides. The final diameter is 100mm and the thickness is 20μm. In order to maintain high hydrogen transmission performance, the thickness of the strengthening film layer should be controlled at about 25μm.

[0049] Specifically, use inorganic high temperature resistant adhesive or brazing method to Figure 4 The composite membrane in the embodiment is attached to the purifier frame to form a monomer purifier. A hydrogen purification test is carried out using the monomer purifier and a test method similar to that in Example 1. Figure 5 The results of the hydrogen purification durability test of the composite membrane prepared in Example 3 at 350°C, an upstream and downstream pressure difference of 20 bar, and a raw gas composition of 90 vol.% H2+10 vol.% CO2 are given.u represents the inlet pressure upstream of the composite membrane, P d represents the inlet pressure downstream of the composite membrane, the horizontal axis is time t, the unit is minutes, written as min. The vertical axis is flow rate J, the unit is molH2 m -2 s -1 , which represents the hydrogen flow rate per unit area per unit time. Figure 5 It can be seen from the results that the composite membrane of this example has a relatively stable hydrogen production rate and good hydrogen purification performance within 600 minutes of working time.

[0050] Example 4:

[0051] This example provides a sheet-like composite membrane of ceramic fiber reinforced membrane layer-vanadium metal purification membrane layer-ceramic fiber reinforced membrane layer for hydrogen purification, comprising an outer reinforced membrane layer of ceramic fiber (crude hydrogen side), an inner reinforced membrane layer of ceramic fiber (pure hydrogen side) and a dense V metal purification membrane layer.

[0052] Specifically, after mechanical grinding and polishing, the vanadium metal is chemically plated with a 100nm thick palladium catalyst layer on both sides. The final diameter is 100mm and the thickness is 20μm. In order to maintain high hydrogen transmission performance, the thickness of the strengthening film layer should be controlled at about 40μm.

[0053] Specifically, the composite membrane is bonded to the purifier frame by using an inorganic high temperature resistant adhesive or by brazing to form a monomer purifier. A hydrogen purification test is conducted using the monomer purifier and a test method similar to that in Example 1. Figure 6 The results of hydrogen purification by the composite membrane at 300°C and 400°C are given. At this time, the upstream pressure is 2-21 bar, the downstream pressure is kept constant at one atmosphere, and the raw gas composition is 85vol.%H2+12vol.%CO2+3vol.%H2O.

[0054] In the above examples, the product hydrogen purified by the purifier is tested by a gas spectrometer, and its purity is greater than 99.999%.

[0055] In summary, the present application provides a high-strength and high-toughness hydrogen separation composite membrane, including a purification membrane layer, characterized in that an inner strengthening membrane layer is arranged on the raw gas side of the purification membrane layer and an outer strengthening membrane layer is arranged on the purified gas side of the purification membrane layer; the thickness of the purification membrane layer is 20 to 50 μm; the thickness of the inner strengthening membrane layer or the outer strengthening membrane layer is 20 to 40 μm, preferably 25 μm. Furthermore, at least one of the hydrogen production catalyst and the carbon capture catalyst is loaded on the inside and at least one part of the surface of the inner strengthening membrane layer. The utility model adds strengthening membrane layers on both sides of the metal film without changing the high hydrogen permeability of the metal film, which not only improves the overall strength and toughness of the film, but also improves the packaging ability.

[0056] The above describes the preferred embodiments of the utility model. It should be understood that the utility model is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solution of the utility model without departing from the scope of the technical solution of the utility model, or modify it into an equivalent embodiment of equivalent changes, which does not affect the essential content of the utility model. Therefore, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the utility model without departing from the content of the technical solution of the utility model still falls within the scope of protection of the technical solution of the utility model.

Claims

1. A hydrogen separation composite membrane, comprising a purification membrane layer (102), characterized in that: An outer strengthening membrane layer (101) is arranged on the raw gas side of the purification membrane layer (102) and an inner strengthening membrane layer (103) is arranged on the purified gas side of the purification membrane layer (102); the thickness of the purification membrane layer (102) is 20 to 50 μm; the thickness of the outer strengthening membrane layer (101) or the inner strengthening membrane layer (103) is 20 to 40 μm.

2. A hydrogen separation composite membrane according to claim 1, characterized in that: The composite film is in the shape of a sheet or a tube.

Citation Information

Cited By

  • High-entropy metal hollow composite fiber membrane and application of high-entropy metal hollow composite fiber membrane in hydrogen production from raw gas

    CN121244011A